Intra-day and inter-day reliabilities of the 0° and 45° adductor squeeze tests using hand-held dynamometry - Kirwan, E.; Nulty, C.; Browne, D. (Sport Sciences for Health, 2023)
Purpose Determine the intra-day and inter-day reliabilities of the 0° and 45° short-lever adductor squeeze tests using hand-held dynamometry.